The Temperature-Dependent Expression of the High-Pathogenicity Island Encoding Piscibactin in Vibrionaceae Results From the Combined Effect of the AraC-Like Transcriptional Activator PbtA and Regulatory Factors From the Recipient Genome - Lages, Marta A.; Lemos, Manuel L.; Balado, Miguel (Frontiers in Microbiology, 2021)
The high-pathogenicity island irp-HPI is widespread among Vibrionaceae encoding the piscibactin siderophore system. The expression of piscibactin genes in the fish pathogen Vibrio anguillarum is favored by low temperatures. However, information about the regulatory mechanism behind irp-HPI gene expression is scarce. In this work, in-frame deletion mutants of V. anguillarum defective in the putative regulators AraC1 and AraC2, encoded by irp-HPI, and in the global regulators H-NS and ToxRS, were constructed and their effect on irp-HPI gene expression was analyzed at 15 and 25°C. The results proved that only AraC1 (renamed as PbtA) is required for the expression of piscibactin biosynthesis and transport genes. PbtA inactivation led to an inability to grow under iron restriction, a loss of the outer membrane piscibactin transporter FrpA, and a significant decrease in virulence for fish. Inactivation of the global repressor H-NS, which is involved in silencing of horizontally acquired genes, also resulted in a lower transcriptional activity of the frpA promoter. Deletion of toxR-S, however, did not have a relevant effect on the expression of the irp-HPI genes. Therefore, while irp-HPI would not be part of the ToxR regulon, H-NS must exert an indirect effect on piscibactin gene expression. Thus, the temperature-dependent expression of the piscibactin-encoding pathogenicity island described in V. anguillarum is the result of the combined effect of the AraC-like transcriptional activator PbtA, harbored in the island, and other not yet defined regulator(s) encoded by the genome. Furthermore, different expression patterns were detected within different irp-HPI evolutionary lineages, which supports a long-term evolution of the irp-HPI genomic island within Vibrionaceae. The mechanism that modulates piscibactin gene expression could also be involved in global regulation of virulence factors in response to temperature changes.